2016
DOI: 10.1134/s000629791613006x
|View full text |Cite
|
Sign up to set email alerts
|

Myosin light chain kinase MYLK1: Anatomy, interactions, functions, and regulation

Abstract: This review discusses and summarizes the results of molecular and cellular investigations of myosin light chain kinase (MLCK, MYLK1), the key regulator of cell motility. The structure and regulation of a complex mylk1 gene and the domain organization of its products is presented. The interactions of the mylk1 gene protein products with other proteins and posttranslational modifications of the mylk1 gene protein products are reviewed, which altogether might determine the role and place of MLCK in physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 184 publications
0
20
0
3
Order By: Relevance
“…Myosin light chain kinase (MYLK) regulates myosin activity through phosphorylation and dephosphorylation of the myosin light chain. Therefore, it is involved in many physiological processes, such as cell adhesion, cell proliferation, cell migration and infiltration (44). MYLK can increase the expression of epidermal growth factor receptor and activate the ERK/JNK signal pathway, which can ablate the adhesion between cells and increase the aggressiveness of breast cancer cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…Myosin light chain kinase (MYLK) regulates myosin activity through phosphorylation and dephosphorylation of the myosin light chain. Therefore, it is involved in many physiological processes, such as cell adhesion, cell proliferation, cell migration and infiltration (44). MYLK can increase the expression of epidermal growth factor receptor and activate the ERK/JNK signal pathway, which can ablate the adhesion between cells and increase the aggressiveness of breast cancer cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from melanoma, AP-1/TEAD modulates the expression of a core set of genes involved in the migration and invasion of different types of cancer cells, including neuroblastoma, colorectal or lung cancer 42 . Regarding the AP-1 transcriptional targets it is worth noting that melanoma cells failing to die up-regulate several genes such as PTX3 , MYLK , SPP1 or RAC2 , all shown to be regulated by AP-1 and involved in metastasis 43 44 45 46 . While in these studies the AP-1/c-JUN transcription factors are activated by a plethora of stimuli such as cytokines, growth factors, UV irradiation or activating mutations in N-RAS and B-RAF genes, in our case, JNK activation was most probably induced as a consequence of minority MOMP 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The mylk-1 gene encodes a 220 kDa MLCK, a 130 kDa MLCK and telokin, and is widely expressed in a diverse range of tissues and cells (18,19). MLCK is involved in adhesion and migration, which are basic characteristics of cells (20,21). A previous pharmacological study revealed that the inhibition of MLCK changed cell motility and wound contraction (22).…”
Section: Discussionmentioning
confidence: 99%